GROWTH PERFORMANCE, INTESTINAL MORPHOMETRICS AND BLOOD PROFILE OF Clarias gariepinus JUVENILES FED MORINGA OLEIFERA SEED MEAL SUPPLEMENT - ORISASONA , O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2021)
The use of antibiotic growth promoters in fish production have resulted in aquatic ecosystem distortion, bioaccumulation of antibiotics in biological systems and development of antibiotic-resistant strains of pathogenic microbes, hence the need for alternatives. This study investigates the effect of Moringa oleifera seed meal as a potential growth promoter in the diet of Clarias gariepinus. Five experimental diets were formulated, with M. oleifera seed meal varied inclusion levels of 0%, 0.5%, 1.0%, 1.5% and 2.0% (diets M0, M0.5, M1.0, M1.5 and M2.0 respectively). Diets were fed to three hundred C. gariepinus (9.50 ±0.50g) randomly allotted to fifteen plastic tanks at twenty fish per 20L tank. The five diets were fed to triplicate groups of fish for 84 days at 3% body weight daily. Mean weight gain (MWG), Feed conversion ratio (FCR), Specific growth rate (SGR) and Survival rate were determined using standard procedures. Blood samples per treatment were subjected to haematological and serum biochemical analysis. Results show that M. oleifera did not significantly affect all growth variables across treatments, although final weight and mean weight gain were marginally higher in M.05 (33.62 and 23.01g respectively) and M1.0 (32.47 and 24.28g respectively) groups and the least values recorded in M2.0 (26.22 and 16.85g respectively). Packed Cell Volume, Haemoglobin count, Red Blood Cell count, Mean Corpuscular Volume, Mean Corpuscular Haemoglobin, and Monocyte count were not significantly different for all treatments (P>0.05). Aspartate aminotransferase levels were lowest in treatment M1.5 with a mean value of 41.00µl and highest in M0 (66.50µl). Alanine transaminase levels also followed the same trend with the lowest value recorded in M1.5 (31.00µl) and the highest value in M0 (55.50µl). The results indicate that Moringa oleifera seed meal as additives in the diet of Clarias gariepinus did not significantly affect the growth and nutrient utilization, but the reduction in ALT and AST values indicate better liver function, stress reduction and possible resistance to diseases.